A mathematical model of the impact of insulin secretion dynamics on selective hepatic insulin resistance. Issue 1 (December 2017) - Zhao, Gang; Wirth, Dagmar; Schmitz, Ingo; Meyer-Hermann, Michael
Abstract Physiological insulin secretion exhibits various temporal patterns, the dysregulation of which is involved in diabetes development. We analyzed the impact of first-phase and pulsatile insulin release on glucose and lipid control with various hepatic insulin signaling networks. The mathematical model suggests that atypical protein kinase C (aPKC) undergoes a bistable switch-on and switch-off, under the control of insulin receptor substrate 2 (IRS2). The activation of IRS1 and IRS2 is temporally separated due to the inhibition of IRS1 by aPKC. The model further shows that the timing of aPKC switch-off is delayed by reduced first-phase insulin and reduced amplitude of insulin pulses. Based on these findings, we propose a sequential model of postprandial hepatic control of glucose and lipid by insulin, according to which delayed aPKC switch-off contributes to selective hepatic insulin resistance, which is a long-standing paradox in the field. Dysregulation of insulin secretion dynamics plays a role in diabetes development. Here, the authors build a mathematical model of hepatic insulin signaling and propose a sequential model of post-meal control of glucose and lipids, according to which delayed aPKC suppression would contribute to selective hepatic insulin resistance.